CHANGES IN BLOOD METABOLITES OF EARLY WEANED NILI-RAVI BUFFALO (B UBALUS BUBALIS) CALVES - M. A. Rashid; T. N. Pasha; M. A. Jabbar; A. Ijaz (Journal of Animal and Plant Sciences, 2013)
Study was conducted to evaluate the effect of age and sampling time on blood metabolites of early weaned Nili-Ravi male buffalo (Bubalus bubalis) calves. Eight newly born, male buffalo calves were fed on colostrum for the first 3 days; thereafter, whole milk was fed at 10% of BW for 6 weeks and intakes were adjusted according to live BW on a weekly basis. At week 7 and 8 calves were fed at 5% and 2.5% of BW, respectively, and weaned off milk at the end of week 8. Calf starter was offered ad-libitum from week 2 through 12 and intakes were recorded on a daily basis. Jugular blood samples were collected 30 minutes before (-30) feeding, at the time of feeding (0), 30, 60 and 90 minutes post morning feeding (+30, +60 and +90). Sampling was conducted at week 4, 8 and 12 of age. Results revealed that blood glucose concentration decreased (P<0.01) with advancing age. Blood urea nitrogen (BUN) concentration increased (P<0.01) with advancing age and was higher at week 8 and 12 (P<0.05) compared with the concentration at 4 week of age. The concentration of plasma NEFA was highest at week 8 and lowest at week 12 (P<0.05). Changes in blood metabolites with advancing age in calves weaned earlier at 8 weeks of age indicate the association between rumen fermentation and blood metabolites that can be used as an indicator for rumen development.
Keywords: Buffalo calf; Milk feeding; Early weaning; Starter; Blood metabolites